1997
DOI: 10.1210/en.138.8.3402
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Period for Thyroid Hormone Action on Seasonal Changes in Reproductive Neuroendocrine Function in the Ewe

Abstract: Thyroid hormones are obligatory for the annually recurring termination of reproductive activity in a spectrum of seasonal breeders, including sheep. Previous studies involving thyroidectomy and T4 replacement have led to the hypothesis that, in the ewe, thyroid hormones are necessary only during a limited interval late in the breeding season for the neuroendocrine processes that cause the transition to anestrus. The present series of experiments tested this hypothesis by assessing the influence of thyroidectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 0 publications
1
25
1
3
Order By: Relevance
“…Similar but less-pronounced effects have been obtained in sheep rendered hypothyroid, in which the end of the reproductive season occurred later than in controls (Follett and Potts, 1990; Hernandez et al, 2003). TH are necessary during a limited period late in the breeding season to permit transition to seasonal anoestrus (Thrun et al, 1996 and1997a), acting primarily within the brain to promote inhibition of neuroendocrine reproductive function (Viguié et al, 1999). TH permit the increase of the responsiveness to the oestradiol negative feeback, but are also required for steroid-independent seasonal cycles in luteinising hormone pulse frequency (Anderson et al, 2002).…”
mentioning
confidence: 99%
“…Similar but less-pronounced effects have been obtained in sheep rendered hypothyroid, in which the end of the reproductive season occurred later than in controls (Follett and Potts, 1990; Hernandez et al, 2003). TH are necessary during a limited period late in the breeding season to permit transition to seasonal anoestrus (Thrun et al, 1996 and1997a), acting primarily within the brain to promote inhibition of neuroendocrine reproductive function (Viguié et al, 1999). TH permit the increase of the responsiveness to the oestradiol negative feeback, but are also required for steroid-independent seasonal cycles in luteinising hormone pulse frequency (Anderson et al, 2002).…”
mentioning
confidence: 99%
“…In seasonal sheep, the responsiveness of the neuroendocrine system, which regulates reproductive activity to thyroid hormones is strongly limited to the particular time of the year. The minimal effective duration of exposure to THs required for the transition to anestrus was estimated to be 60-90 days (Thrun et al 1997). In thyroidectomized ewes, replacement of T4 beginning in late December was found to be the only time of year that THs were effective in seasonal changes of reproductive activity (Thrun et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The minimal effective duration of exposure to THs required for the transition to anestrus was estimated to be 60-90 days (Thrun et al 1997). In thyroidectomized ewes, replacement of T4 beginning in late December was found to be the only time of year that THs were effective in seasonal changes of reproductive activity (Thrun et al 1997). In our study we began the CSF collection in December and finished in March, when all ewes entered anestrus according to the decrease in progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical sheep breeds, the highest T 4 profiles were recorded in the summer (Ashutosh et al, 2001), andRhind et al (2000) observed that T 4 concentrations were higher in the spring and summer than in the autumn. Thrun et al (1997) hypothesized that, to promote seasonal reproductive suppression in the ewe, thyroid hormones are necessary only during a short interval late in the breeding season and the reproductive neuroendocrine axis is not equally responsive to thyroid hormones at all times of the year. If that is true, it suggests there is a critical period of responsiveness during which thyroid hormones must be present for anoestrus to develop, and it might explain the different seasonal patterns in the secretion of T 4 reported in the literature.…”
Section: A B Cmentioning
confidence: 99%